The Famous Five Five go off in a caravan - Blyton, Enid; Soper, Eileen Alice (Hodder Children's London, 1997)
Julian, Dick, Anne, George and Timmy the dog find excitement and adventure wherever they go in Enid Blyton's most popular series.